ANALISIS PENGARUH PERKEMBANGAN UMKM TERHADAP PENYERAPAN TENAGA KERJA DI KABUPATEN GOWA (STUDI KASUS PADA UMKM SEKTOR KULINER DI KECAMATAN SOMBA OPU DAN PALLANGGA - Sukma Wulandari; Sry Astuti; Regina, Regina; Muh Syafri; Citra Ayni Kamaruddin (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to analyze the influence of the development of culinary MSMEs on labor absorption. This study was conducted in Somba Opu and Pallangga Districts, Gowa Regency, which were selected intentionally. The data used in this study are primary cross-section data. The method of determining respondents is by using the Slovin formula, where calculations are carried out to obtain one hundred culinary MSMEs with business actors as respondents. The research method used is the causal associative method with a quantitative approach. Data collection methods are observation and direct interviews with questionnaire guidance. Data analysis techniques use multiple linear analysis. Based on the results of this study, simultaneously, the indicators of the development of culinary MSMEs in Somba Opu and Pallangga Districts have an effect on labor absorption.